Therapeutic potential of silver nanoparticles from Helianthemum lippii extract for mitigating cadmium-induced hepatotoxicity: liver function parameters, oxidative stress, and histopathology in wistar rats - Laib, Ibtissam; Ali, Boutlilis Djahra; Alsalme, Ali; Croun, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: This study explores the therapeutic potential of silver nanoparticles (Ag NPs) synthesized using a Helianthemum lippii extract in mitigating cadmium-induced hepatotoxicity in Wistar rats. Given the increasing environmental and health concerns associated with cadmium exposure, novel and eco-friendly therapeutic strategies are essential. Methods: Ag NPs were characterized using X-ray diffraction, UV-Vis spectrometry, and energy-dispersive X-ray spectroscopy with scanning electron microscopy, confirming their formation with a cubic crystal structure and particle sizes ranging from 4.81 to 12.84 nm. A sub-acute toxicity study of Ag NPs (2 mg/kg and 10 mg/kg) was conducted, showing no significant difference compared to untreated control rats (n = 3 animals/group). Subsequently, adult Wistar rats (n = 5/group) were divided into a control group and three experimental groups: Ag NPs alone, exposure to 50 mg/kg CdCl2 in drinking water for 35 days, and CdCl2 exposure followed by 0.1 mg/kg/day Ag NPs intraperitoneally for 15 days. Results: In the CdCl2-exposed group, there was a significant decrease in body weight and increases in alanine and aspartate transaminase levels (p < 0.05 vs. control), indicating hepatotoxicity. Additionally, antioxidant defenses were decreased, and malondialdehyde levels were elevated. Liver histology revealed portal fibrosis, inflammation, necrosis, sinusoid and hepatic vein dilation, and cytoplasmic vacuolations. Treatment with Ag NPs post-CdCl2 exposure mitigated several adverse effects on liver function and architecture and improved body weight. Discussion: This study demonstrates the efficacy of Ag NPs synthesized via a green method in reducing cadmium-induced liver damage. These findings support the potential of Ag NPs in therapeutic applications and highlight the importance of sustainable and eco-friendly nanoparticle synthesis methods. By addressing both toxicity concerns and therapeutic efficacy, this research aligns with the growing emphasis on environmentally conscious practices in scientific research and healthcare.